2014
DOI: 10.2478/manment-2014-0041
|View full text |Cite
|
Sign up to set email alerts
|

The Intuitive Manager and the Concept of Strategic Leadership

Abstract: Summary The aim of this paper is to show the consistency of an intuitive manager’s traits and skills and a strategic leader’s attributes. The paper consists of three main parts. The first one presents the nature and evolution of the concept of leadership and contrasts the role of strategic leaders with the operational requirements of modern organizations. In the second part, we attempt to define the concept of intuition and characterize an intuitive manager. In the last section of the paper, a strategic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Ethical leadership has a positive and significant impact on employee productivity. Training and development has a positive effect on employee performance by improving their skills and capabilities (Dittrich-Lagadec et al, 2010;Malewska & Sajdak, 2014). Results of the paper from (Mnasi et al, 2022) stated that mentoring practices such as acceptance, sponsorship, delegation, and relationship have a positive and economic contribution to the employee performance model in local government agencies at 95% confidence interval.…”
Section: Resultsmentioning
confidence: 99%
“…Ethical leadership has a positive and significant impact on employee productivity. Training and development has a positive effect on employee performance by improving their skills and capabilities (Dittrich-Lagadec et al, 2010;Malewska & Sajdak, 2014). Results of the paper from (Mnasi et al, 2022) stated that mentoring practices such as acceptance, sponsorship, delegation, and relationship have a positive and economic contribution to the employee performance model in local government agencies at 95% confidence interval.…”
Section: Resultsmentioning
confidence: 99%
“…However, the dimension of intuition seems to be outside the ability to participate in leadership thinking quite clearly (M=1.64), while studies have revealed the important role of intuition in leadership. This is stated by Malewska and Sajdak (2014) [70] who said that in leadership when there is not enough data to analyze and evaluate the problem for leadership decision making, the leader can rely on the advice of intuition, even intuition in female leadership is quite sensitive in senior female managers [71]. Storsteen (2019) [72] reveals intuition as a key ingredient for innovation, performance, and informed leadership.…”
Section: -2-the Status Of Transformational Leadership Style and Leadership Thinkingmentioning
confidence: 99%
“…Indeed, leaders interact with several resources, including human resources, with such as a youthful workforce. Malewska and Sajdak (2014) explained that strategic leadership is about designing and implementing long-term strategies to overcome future uncertainties and help in achieving the goal of continuous development. They also indicated that strategic leadership focuses on continuous improvement through sharing knowledge, and through showing the ability to overcome difficulties and predict and handle the change effectively.…”
Section: Review Of Literaturementioning
confidence: 99%
“…They also indicated that strategic leadership focuses on continuous improvement through sharing knowledge, and through showing the ability to overcome difficulties and predict and handle the change effectively. Malewska and Sajdak (2014) stressed that strategic leadership shows the ability to overcome uncertainty and deal with unpredicted change in an organization or a market.…”
Section: Review Of Literaturementioning
confidence: 99%